UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY MEDIA IN DISTANCE LEARNING IN THE UPPER GRADE OF ELEMENTARY SCHOOL - Tissa Maharani (Asosiasi Dosen Muda Indonesia, 2023)
Along with the Covid-19 pandemic and the issuance of a Circular Letter from the Minister of Education and Culture regarding the Implementation of Education in an Emergency Period, the Indonesian education system has also adapted by implementing distance learning. This distance learning forces teachers and students to change the concept of learning in class to learning in cyberspace using existing information and communication technology media. This study aims to identify and explain what information and communication technology media are used in distance learning in the upper grades of elementary schools, and how to implement their use. The collection of research data uses the library study method and uses secondary data collected from articles, and journals. The criteria for the selected data are regarding the utilization of information and communication technology media in the upper grades of elementary schools during distance learning From several sources obtained, finally the most relevant was selected and 13 articles were obtained. The results of this literature study research are information and communication technology media used during distance learning in upper grades in several elementary schools are Zoom, Google Classroom, gadgets, animated videos, Google Forms, Google Sites, Quizizz, MS 365, WhatsApp, WPS, Youtube and the Rumah Belajar portal. Blended learning and e-learning systems are also worth trying to use in distance learning.